Critical Analysis of Contemporary Structuralism - Kursanovas, Georgijus (Problemos, 1974)
The well-known Soviet philosopher, G. A. Kursanov, in his paper “Critical Analysis of Contemporary Structuralism” presents a critical analysis of the methodological principles of structuralistic theories. The author notes such defects of the structuralist methodology: first, structuralism isolates social structures from actual conditions of their existence; it converts these structures into autonomic entities, second, it absolutizes the role and meaning of linguistic structures; third, many structuralists regard social structures to be invariable, finished and given; fourth, structuralism excludes the active human social-historical activity generating all social structures. At the same time G. A. Kursanov points out the positive scientific results related with the use of the structural method in special fields of research. First or all, the rational element is constituted by the systematic approach to the objects investigated. Secondly, structural analysis of linguistic phenomena provides possibility for determining real aspects of life of human society, most distinctly expressed in various linguistic complexes and relations (the latter seem to be “naturally” patterning theses aspects). Finally, structuralism has advantage over philosophical subjectivism and apriorism, for it rests upon the analysis of the objectively existing social, economic, linguistic and other structures. In general the claims of structuralism to be the universal method of cognition and tendencies to consider it as a new philosophical world-view adequate to the scientific concept of natural and social phenomena remain untenable.